Control of Mould Spoilage on Apples Using Yeasts as Biological Control Agents - Zukisani Gomomo; Morris Fanadzo; Maxwell Mewa-Ngongang; Justin Hoff; Marieta Van der Rijst; Vincent Okudoh; Johan Kriel; Heinrich W. du Plessis (Polish Journal of Food and Nutrition Sciences)
Considerable quantities of fruit are lost during pre- and post-harvest stages due to mould spoilage. The aim of this study was to evaluate the antagonistic effect of selected yeasts against spoilage mould Botrytis cinerea , Penicillium expansum and Alternaria alstroemeriae . One hundred and four yeast isolates were screened for antagonistic activity against B. cinerea, P. expansum and A. alstroemeriae using radial inhibition, dual and mouth-to-mouth plate assays. Sixty-seven out of 104 yeasts showed growth inhibition activity against P. expansum , while 36 yeasts inhibited B. cinerea , 47 yeasts inhibited A. alstroemeriae, but only 22 yeasts showed inhibition activity against all three moulds. Candida pyralidae Y63, Meyerozyma guilliermondii Y88 and Zygoascus hellenicus Y89 showed highest inhibition activity against all three moulds, when mode of inhibition was due to direct contact. Volatile organic compounds produced by Pichia kluyveri Y64, C. pyralidae Y63 and M. guilliermondii Y88 showed the highest growth inhibition against all three moulds. These yeasts were also evaluated against all three moulds on apples. P. kluyveri Y64 showed 100%, 57% and 26% growth inhibition against A. alstroemeriae, B. cinerea and P. expansum , respectively, on apples and performed slightly better than a commercial fungicide against B. cinerea and P. expansum . While M. guillermondii Y88 showed 100%, 60% and 18% inhibition on apples against A. alstroemeriae, B. cinerea and P. expansum , respectively. P. kluyveri Y64 and M. guilliermondii Y88 showed potential as biofungicides and warrant further investigation.